Prevalence of Urinary Schistosomiasis in Al-Rusafah Regions of Baghdad governarate (Baghdad Science Journal, 2016)
Urinary Schistosomiasis is one of important diseases that cause irritation and damage of urinary tract and other systems and tissues and can not be expected by doctors when diagnosing urinary tract diseases.The current study is conducted to investigate the prevalence of schistosomiasisin Baghdad / Al-Rusafa. 191urine samples were collected fromresidents ofsome areas of Al-Rusafain Baghdad governarate (Almashtal, Albaladyat, Alameen, Baghdad aljadida and Alnahrawan) for the period from March until the end of September 2010.The samples were examined by the precipitation and examination of micro hematuria by reagent strips. The total infection percentage was 9.42% (18/191) and was significantly higher in males compared tofemales12.64% (11/87), 6.73% (7/104) respectivly, and in ages